Assessing Well-being in The Digital Age : A Rasch Model Analysis to Validating Teacher Happiness and Student Mental Health Instruments - Syahri, Akhmad; Dinawisda, Nimatul; Abdullah, Abdullah; Khadavi, Muhammad Jadid; Purnamasari, Rika (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop an instrument for measuring teacher happiness and student mental health in the digital era. A descriptive quantitative method with Rasch model analysis was employed, involving 411 teachers, 1,102 State Senior High School students, and State Madrasah Aliyah students in Mataram City, who completed questionnaires distributed through Google Forms. The results indicate that out of 22 teacher happiness items, 16 were found to be fit, with a person reliability value of 0.46, a separation of 0.92, an item reliability of 0.99, a separation of 10.18, and a construct validity of 56%. For student mental health, 25 out of 28 items were fit, with a person reliability value of 0.79, a separation of 1.94, an item reliability of 1.00, a separation of 19.58, and a construct validity of 34%. These findings suggest that the instruments are valid for measuring teacher happiness and student mental health in the digital era. The study implies the need for educational policies supporting teachers’ and students’ psychological well-being, such as integrating teacher happiness training programs and implementing data-driven digital monitoring of student mental health. Such policies are essential for fostering a healthy and adaptive learning environment in the digital transformation era.